Proactive spectrum handoff protocol for cognitive radio ad hoc network and analytical evaluation. Issue 15 (1st October 2015) - Mehrnoush, Morteza; Fathi, Reza; Vakili, Vahid T.
Abstract : Spectrum handoff in cognitive radio technology has been emerged as a new method for improving performance of the cognitive radio networks. The authors propose a proactive spectrum handoff protocol based on a single rendezvous (SRV) coordination scheme without common control channel. This protocol utilises a multi‐user greedy channel selection method to select the best channel based on minimum service time for the secondary users to achieve a higher aggregate throughput. The authors proposed a novel theoretical analysis to evaluate the aggregate throughput of the secondary users in the proposed protocol. It uses Markov Chain to model the distributed channel selection scheme. The simulation results show the proposed protocol increases the throughput up to 38.7% in comparison with the study by Song and Xie, for 12 secondary users in the network with transmission rates of primary and secondary users equal to 5 (pkt/s) and 500 (pkt/s), respectively.